Trust, integrated information technology and new product success. Issue 3 (14th August 2017) - Ettlie, John E.; Tucci, Christopher; Gianiodis, Peter T.
Abstract : Purpose: The purpose of this paper is to investigate the combined roles via trust relationships of the two technology cores of the firm: information technology (IT) and R&D and their impact on new product success. Design/methodology/approach: A model was tested whereby trust and the integrated IT strategy account for a significant amount of the variance in a broad range of new product development (NPD) outcomes for a survey sample of 223 manufacturing firms. Respondents said design practices and quality methods like Six Sigma accounted for a total of over 25 percent of the reports of the most helpful approaches in promoting effective NPD. At the same time their biggest challenges were having a clear strategic direction within which to operate and resolving cost and resource issues which accounted for over a third (34 percent) of barriers to success. Findings: Respondents reported that a total of over 25 percent of the reports of the most helpful approaches in promoting effective included these quality methods. At the same time their biggest challenges were having a clear strategic direction within which to operate and resolving cost and resource issues which accounted for over a third (34 percent) of barriers to success. High-tech firms were less likely to report integrated IT strategies, but this tended to be counterbalanced by high levels of trust in the IT function and adoption of organizational innovations for execution of strategic intent. Implications for future research and practice are discussed. Research limitations/implications: Survey methods produce broad results with low response rates in most studies involving R&D and NPD, and this study is no exception. Practical implications: With the challenge of strategy alignment reported by many of these firms, it seems clear that the top management team cannot afford to leave NPD challenges to engineering teams and NPD programs without guidance and general vision. Social implications: NPD has become the staple of most manufacturing firms as a way of meeting and beating the competition worldwide. However, trust between functional areas often starts before people are even employed and should begin in training and educational programs. Originality/value: Designing NPD programs is at the heart of many firms' competitive strategies and the fast learning companies are the winners. Very little is known about the trust relationship between IT and R&D and their combined effects on new product success which we have found to be significant and unexpected in their impacts.